(untitled) (Asian Journal of Medical Sciences, 2014)
Background: When the heart faces a hemodynamic burden, increasing mass assumes a key role in the compensation for hemodynamic overload. A strong confounding factor in this relation is the altered ascending aortic haemodynamics in hypertensives due to altered ascending aortic diameter at annulus. Objectives: Ascending aortic diameter has an effect on the after load which may affect the left ventricular function. We studied to investigate the influence of the ascending aortic diameter on the left ventricular function in hypertensives. Improving the haemodynamics in such conditions may reduce mortality rates and result in better quality of life. Material and methods: We conducted a case control study involving hypertensive patients (n=25) and normotensive subjects (n=25) of same age group acting as controls. Ascending aortic diameter was measured at annulus and using M mode echocardiography we measured the thickness of the interventricular septum & posterior wall. Diameter of the ventricle during systole and diastole were obtained. All measurements were taken according to the American Society of Echocardiography recommendation. Results: The measured parameter ejection time(r=0.545, n=25, p= 0.005) and left ventricular internal diameter during diastole (r=0.348, n=25, p= 0.02) showed a very high significant positive correlation with the ascending aortic diameter. Conclusion: We would conclude to say that the reduced ascending aortic diameter has a significant effect on left ventricular wall and left ventricle function in hypertensives. The Doppler evaluation of ascending aortic diameter in hypertensives may help in achieving a reduction in morbidity and mortality due to hypertension induced cardiovascular disorders. DOI: http://dx.doi.org/10.3126/ajms.v5i4.9862 Asian Journal of Medical Sciences 2014 Vol.5(4); 6-10